Skin and soft tissue infections in intercontinental travellers and the import of multi-resistant Staphylococcus aureus to Europe. (June 2015) - Nurjadi, D.; Friedrich-Jänicke, B.; Schäfer, J.; Van Genderen, P.J.J.; Goorhuis, A.; Perignon, A.; Neumayr, A.; Mueller, A.; Kantele, A.; Schunk, M.; Gascon, J.; Stich, A.; et al.
Abstract: Staphylococcus aureus is emerging globally. Treatment of infections is complicated by increasing antibiotic resistance. We collected clinical data and swabs of returnees with skin and soft tissue infections (SSTI) at 13 travel-clinics in Europe (www.staphtrav.eu ). Sixty-two percent (196/318) SSTI patients had S. aureus -positive lesions, of which almost two-thirds (122/196) were Panton–Valentine leukocidin (PVL) positive. PVL was associated with disease severity, including hospitalization for SSTI (OR 5.2, 95% CI 1.5–18.2). In returnees with SSTI, longer travel and more intense population contact were risk factors for nasal colonization with PVL-positive S. aureus . Imported S. aureus frequently proved resistant to trimethoprim-sulfamethoxazole (21%), erythromycin (21%), tetracycline (20%), ciprofloxacin (13%), methicillin (12%) and clindamycin (8%). Place of exposure was significantly (p < 0.05) associated with predominant resistance phenotypes and spa genotypes: Latin America (methicillin; t008/CC24/304), Africa (tetracycline, trimethoprim-sulfamethoxazole; t084/CC84, t314/singleton, t355/CC355), South Asia (trimethoprim-sulfamethoxazole, ciprofloxacin; t021/CC21/318), South-East Asia (clindamycin; t159/CC272). USA300-like isolates accounted for 30% of all methicillin-resistant S. aureus imported to Europe and were predominantly (71%) acquired in Latin America. Multi-resistance to non-β-lactams were present in 24% of imports and associated with travel to South Asia (ORcrude 5.3, 95% CI 2.4–11.8), even after adjusting for confounding by genotype (ORadjusted 3.8, 95% 1.5–9.5). Choosing randomly from compounds recommended for the empiric treatment of severe S. aureus SSTI, 15% of cases would have received ineffective antimicrobial therapy. These findings call for the development of regionally stratified guidance on the antibiotic management of severe imported S. aureus disease and put the infected and colonized traveller at the centre of interventions against the global spread of multi-resistant S. aureus .